Trehalose–whey protein conjugates prepared by structural interaction: Mechanisms for improving the multilevel structure and their water solubility and protein digestibility - Alrosan, Mohammad; Al-Massad, Motasem; Al-Qaisi, Ali; Gammoh, Sana; Alu’datt, Muhammad H.; Al Qudsi, Farah R.; Tan, Thuan-Chew; Razzak Mahmood, Ammar A.; Almajwal, Ali Madi (Italian Journal of Food Science, 2024)
Whey proteins (WPs) are the most widely used protein supplements worldwide. This study investigates the impact of incorporating trehalose into WPs at different ratios ranging from 1% to 5% (w/v) on the structural characteristics, surface properties, and functionality of trehalose (T) conjugated to WPs (T-WP). The T-WP conjugate was produced using the pH-shifting technique. Our findings demonstrated that conjugating trehalose into WPs significantly altered the Fourier-transform infrared (FTIR) spectrum, tertiary structure, and protein conformation. The surface charge and hydrophobicity of T-WPs were changed significantly (p < 0.05). Structural modifications had a notable effect on the solubility and digestibility of T-WPs. The water solubility of T-WPs increased from 88.12% to 95.53% when conjugated with 5% (w/v) trehalose. Furthermore, the impact of the development of T-WPs on FTIR spectrum was investigated. The β-sheet, random coil, α-helix, and β-turn were changed significantly from 36.17% to 45.21%, 12.38% to 16.39%, 10.69% to 13.44%, and 40.76% to 24.94%, respectively. The results presented in this study offer structural information to enhance the creation of WP products with improved functional properties.